1912-2012 El siglo de los comunistas chilenos - Álvarez, Rolando; Ulianova, Olga; Loyola, Manuel (Ariadna Ediciones, 2012)
Compiling dedicated to various aspects of the history of the Communist Party of Chile in its history in the 20th century